Perioperative Sleep Disturbances and Postoperative Delirium in Adult Patients: A Systematic Review and Meta-Analysis of Clinical Trials - Wang, Hongbai; Zhang, Liang; Zhang, Zhe; Li, Yinan; Luo, Qipeng; Yuan, Su; Yan, Fuxia (Frontiers in Psychiatry, 2020)
Background: The aim of this systematic review and meta-analysis of clinical trials was to investigate the effects of perioperative sleep disturbances on postoperative delirium (POD). Methods: Authors searched for studies (until May 12, 2020) reporting POD in patients with sleep disturbances following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: We identified 29 relevant trials including 55,907 patients. We divided these trials into three groups according to study design: 7 retrospective observational trials, 12 prospective observational trials, and 10 randomized controlled trials. The results demonstrated that perioperative sleep disturbances were significantly associated with POD occurrence in observational groups (retrospective: OR = 0.56, 95% CI: [0.33, 0.93], I2 = 91%, p for effect = 0.03; prospective: OR = 0.27, 95% CI: [0.20, 0.36], I2 = 25%, p for effect < 0.001), but not in the randomized controlled trial group (OR = 0.58, 95% CI: [0.34, 1.01], I2 = 68%, p for effect = 0.05). Publication bias was assessed using Egger’s test. We used a one-by-one literature exclusion method to address high heterogeneity. Conclusions: Perioperative sleep disturbances were potential risk factors for POD in observational trials, but not in randomized controlled trials.